6ER-002 Assessement of efficacy of proprotein convertase subtilisin/kexin type 9 inhibitors (i-pcsk9) for hypercholesterolaemia with or without statins. (2nd March 2018) - Aguilar, E; Dani, L; Carmona, I Moya; Estaun, C; Ovies, JM Fernández
Abstract : Background: Proprotein inhibitors convertase subtilisin/kexin9 (i-PCSK9) are new drugs for hypercholesterolaemia used in monotherapy or in combination with statins, which have numerous interactions. It may be useful to study the efficacy of I-PCSK9 as a single therapy. Purpose: To compare the efficacy of i-PCSK9 alirocumab and evolocumab in monotherapy versus bitherapy with statins, in order to define the clinical benefit of deprescribing statins in these patients. Material and methods: A retrospective observational study was conducted in our centre from March 2016 to March 2017. Patients treated with I-PCSK9 with/without combining it with statins were included. Low-density lipoprotein cholesterol (LDL-C) levels were measured before starting the treatment and at weeks 8 and 24. Data were available from medical histories. Adherence was calculated indirectly by consulting the dispensing of statins at the pharmacy office in the application for external prescription of our Autonomous Community. Results: During the study period, 42 patients, 25 males and 17 females, were treated with i-PCSK9 in our centre. Sixteen started i-PCSK9 as a single treatment because of their intolerance to statins. Among the 26 patients who continued their treatment with statins, 58% (15/26) had a treatment adherence of 90%. Forty-two per cent (11/26) of these patients dropped out from treatment with statins before week 8. In the subgroup of patients in treatment with i-PCSK9 in monotherapy (because of lack of adherence or intolerance to statins) the lowering of LDL-C at week 8 (n=10) was compared to patients treated with bitherapy (n=9) (all other patients were excluded because they had not completed 8 weeks of treatment or because of lack of data). An average reduction in LDL-C from a baseline of 57% (95% CI: 40 to 74) and 80% (95% CI: 40 to 74) was obtained respectively. Conclusion: A high rate of patients who start i–PCSK9 therapy do not continue statin treatment. In our study, the reduction in LDL–C with i–PCSK9 as a single agent is similar to the results of the LONG TERM trial (60%) in which only patients with biotherapy were included. Regarding the results obtained and the added complexity of using statins, it seems reasonable to research the efficacy of i–PCSK9 in monotherapy. No conflict of interest